The demand of Public Administration management’s staff competences in the future - Lakstigala, Ineta; Balina, Signe (University of Latvia, 2019)
The development of the competences of the staff of the Latvian Public Administration has been drawing more and more attention. The aim of the development of the human resources is a professional, motivated, advanced and honest staff of the Public Administration. It means that it is necessary to evaluate the competences of the staff in order to upgrade them and understand what is in demand nowadays. Improved personal and professional competences are regularly needed to improve the quality, efficiency, development of creative thinking, knowledge and adaptation to the trends and demands of the 21 st century. It is therefore important to understand whether employees are in line with a specialised profession in order to improve and maintain the skills of employees, who have played an important role in the work process as a result of the rapid development of technology today. It is therefore important to find out what competencies will become an integral part of human work. The aim of the research is to understand, what kind of competences in the future are going to be in demand for Public Administration staff. The methods used in the research work are going to be the analysis of the documents and data analysis. The results of the research are going to be used in practice by evaluating and upgrading the competences of the Public Administration staff.
Keywords: competence; development; staff; Research Subject Categories::SOCIAL SCIENCES::Business and economics